Implementation of Policies For The Management of Household Waste and Waste Similar to Household Waste in Tanjung Unggat Village, Tanjungpinang City - Cyndi Ardanya; Nazaki Nazaki; Ardi Putra (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the implementation of Tanjungpinang Mayor Regulation Number 43 of 2018 concerning Regional Policies and Strategies (Jakstrada) for the Management of Household Waste and Household-Like Waste in Tanjung Unggat Village, Bukit Bestari District, Tanjungpinang City. The research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation, while data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The analysis of policy implementation was based on George C. Edward III’s theory, which consists of four dimensions: communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of the policy has not yet been carried out optimally. The communication dimension has been implemented through socialization activities, coordination mechanisms, and information media; however, the dissemination of information has not reached all community members evenly. The resource dimension continues to face limitations in terms of the quantity and capacity of human resources, budget allocation, and supporting facilities and infrastructure. In terms of disposition, implementers demonstrate a strong commitment to carrying out the policy, although its effectiveness is still influenced by low levels of public awareness and the inadequate enforcement of sanctions. Regarding the bureaucratic structure dimension, the division of responsibilities among relevant agencies has been established, but it is not yet supported by more detailed standard operating procedures, continuous inter-agency coordination, and an integrated monitoring system. Therefore, strengthening communication, enhancing resource capacity, improving operational procedures, reinforcing inter-institutional coordination, and increasing community participation are necessary to support more effective and sustainable waste management.